If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying x + -45 = -24 Reorder the terms: -45 + x = -24 Solving -45 + x = -24 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '45' to each side of the equation. -45 + 45 + x = -24 + 45 Combine like terms: -45 + 45 = 0 0 + x = -24 + 45 x = -24 + 45 Combine like terms: -24 + 45 = 21 x = 21 Simplifying x = 21
| -4x+5y=-41 | | r(r+11)=42 | | 7(8c-1)-8=54c+7 | | x-7.8=-6.8 | | 5x-2.5(7-4x)=x-7(4+x) | | 5x-4=7x+2 | | z+27=21 | | 6x^2-72x+220=0 | | 5y^2-3xy+2x=4 | | s^2-45-12=0 | | px+qx=1 | | (3-x)/(x-8)-(2x+4)/(8-x) | | 6+4s-5=8s+5-2s | | 81=27q | | 4x+4=-x+39 | | 2(x^2*2)=1 | | x+3.00=11.00 | | 5-2k=21+6k | | 3(x-2)=48 | | 10t=50 | | 35x^2+48x-27= | | n+3/8=7/10 | | 14x+4=16x-6 | | z/3+5=z/2+7 | | 1/8n+6=-5/8(n-16) | | n+3/58=7/10 | | n^2-2n+1=25 | | 30(20y-3)=194-y | | 2y/19y | | 21*10-6*10= | | 14x+14(3-2x)+7=4-x+5(2-3x) | | 14x=y-4 |